2004
DOI: 10.1007/s00493-004-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

Nowhere-Zero 4-Flows, Simultaneous Edge-Colorings, And Critical Partial Latin Squares

Abstract: It is proved in this paper that every bipartite graphic sequence with the minimum degree δ ≥ 2 has a realization that admits a nowhere-zero 4-flow. This result implies a conjecture originally proposed by Keedwell (1993) and reproposed by Cameron (1999) about simultaneous edge-colorings and critical partial Latin squares.A corollary of Theorem 1.1 solves a conjecture originally proposed by Keedwell [5] and reproposed by Cameron [2]. Theorem 1.2. (Keedwell-Cameron Conjecture)Every bipartite graphic sequence S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…(• means the cell is empty.) In fact, T is the Latin bitrade corresponding to a 2-simultaneous edge coloring of the graph G that showed in Figure 1 Since Luo et al in [11] showed that each bipartite graphic sequence S with all its elements greater than 1, has a 2-simultaneous edge colorable bipartite realization, we have…”
Section: µ-Simultaneous Edge Coloring and µ-Way Latin Tradementioning
confidence: 99%
See 1 more Smart Citation
“…(• means the cell is empty.) In fact, T is the Latin bitrade corresponding to a 2-simultaneous edge coloring of the graph G that showed in Figure 1 Since Luo et al in [11] showed that each bipartite graphic sequence S with all its elements greater than 1, has a 2-simultaneous edge colorable bipartite realization, we have…”
Section: µ-Simultaneous Edge Coloring and µ-Way Latin Tradementioning
confidence: 99%
“…Also, they conjectured that every bridgeless bipartite graph is 2-simultaneous edge colorable. Luo et al in [11] showed that every bipartite graphic sequence S with all its elements greater than one, has a realization that admits a 4-NZF. Thus, by Theorems A (iii) and B, they proved that the SE conjecture is true.…”
Section: Introductionmentioning
confidence: 99%
“…Jaeger [2] proved that every 4-edge connected graph has a 4-NZF. In [3], the authors showed that if every edge of a graph G is contained in a cycle of length at most 4, then G admits a 4-NZF. In this paper, we determine the exact minimum flow number of G ∨ H for all graphs G and H.…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively studied whether a degree sequence has a realization with certain properties. A noticeable application (see [64]) of graph realization with 4-flows has been found in the design of critical partial Latin squares which leads to the proof of the socalled simultaneous edge-coloring conjecture by Keedwell [41] and Cameron [14]. All graphic sequences which have realizations admitting a nowhere-zero 3-flow or 4-flow are characterized in [63] and [64], respectively.…”
Section: Graphic Degree Sequences With Z K -Connected Realizationsmentioning
confidence: 99%